2011
DOI: 10.1007/s00210-011-0613-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antioxidative effect of isoquercitrin on cadmium-induced oxidative damage to mouse liver and kidney

Abstract: Cadmium (Cd) is an environmental pollutant and has been found to pose a potential threat to human health. Isoquercitrin (IQ) is one of the most important flavonoids and has been demonstrated to exhibit potent antioxidant effects on plants and yeast cells. However, only few studies have investigated the antioxidative activities of reactive oxygen species (ROS) and the nitrite scavenging activities of IQ against Cd-induced oxidation in mouse. The present work was to investigate the ROS and nitrite-scavenging act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 46 publications
(50 reference statements)
0
51
1
1
Order By: Relevance
“…27 Several studies have reported that pretreatment with isoquercitrin increased the cell tolerance to oxidative stress. [28][29][30] Along with this, flavonoids with antioxidant activity such as quercetin have a high binding affinity towards catalase enzyme in the cells. 29 The binding of quercetin with catalase induced some conformational changes on this enzyme, which results in enhanced ability to quench free radicals as well as increase the antioxidant status in cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have reported that pretreatment with isoquercitrin increased the cell tolerance to oxidative stress. [28][29][30] Along with this, flavonoids with antioxidant activity such as quercetin have a high binding affinity towards catalase enzyme in the cells. 29 The binding of quercetin with catalase induced some conformational changes on this enzyme, which results in enhanced ability to quench free radicals as well as increase the antioxidant status in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin absolutely prevented mercury chloride (HgCl 2 )-induced kidney injury of SpragueeDawley rats (Shin et al, 2015). Similarly, isoquercitrin (IQ) possessed ROS and nitrite-scavenging capacities and played a significant role in combating Cd(2þ)-induced toxicity in animals (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This action is mediated by numerous mechanisms including the follow ing: Protecting the cell membrane by inhibiting LDH efflux [34] ; maintaining erythrocyte deformability, which plays an essential role in circulatory system by preventing vascular diseases [35] ; accumulating in the arterial wall and preventing hyperlipidemia [36] ; inhibiting fatty acid formation resulting from lipid peroxidation [37] ; protecting neural cells against oxidative stress induced by H2O2 by Orfali GC et al . Isoquercitrin in cancer decreasing lipid peroxidation and increasing cellular chole sterol concentrations [38] ; reducing glutathione depletion and decreasing catalase and glutathione peroxidase 1 activities [39] ; ROS and nitritescavenging activities [40] ; and by regulating the oxidative complex NADPH and NO production [41] , lipidlowering activities in hepatocytes [42] , induction of apolipoprotein AI gene expression [43] , and free radical scavenging [4464] .…”
Section: Effects Of Iq In Cancermentioning
confidence: 99%